Lee 3 Tau Ceti Central Armory Show. - Chambaud, Etienne; Eliade, Mircea; Ensor, James; Grosz, George; Jaccottet, Philippe; Magnin, Stéphane; Maire, Benoît; Pound, Ezra; Tenret, Yves; Wahler, Marc-Olivier (Nice : Villa Arson Nice, 2003)
Ancelin, David ; Aubouin, Patrick ; Barré, Virginie ; Bauchet-Coquatrix, Frédéric ; Baudevin, Francis ; Baxter, Glen ; Blanc, Jean-Luc ; Bonvicini, Monica ; Bouillon, Julien ; Bueno, Sophie ; Trannois, Niels ; Calais, Stéphane ; Chambaud, Etienne ; Cook, Colin ; Shambaugh, Bill ; Coste, Annelise ; Curlet, François ; cussol, Béatrice ; Dafflon, Stéphane ; Dass ; Decrauzat, Philippe ; Dejode, Sophie ; Lacombe, Bertrand ; Delvoye, Wim ; Detourne, Nathalie ; Dolla, Noël ; Duyckaerts, Eric ; Khazem, Jean-Pierre ; Errò ; Fauguet, Richard ; Filliou, Robert ; Flexner, Roland ; Forstner, Gregory ; Gastaldon, Vidya ; Ghelloussi, Karim ; Gygi, Fabrice ; Hamu, Aïcha ; Hatoum, Mona ; Hektor ; Julien, Jacques ; Kentridge, William ; Kilimnik, Karen ; Kippenberger, Martin ; Klat ; Klossowski, Pierre ; Kolk, Douglas ; Krystufek, Elke ; Lang, Sabina ; Baumann, Daniel ; Le Gentil Garçon ; Levi, Renée ; Loutz, Frédérique ; Luche, Ingrid ; Magnin, Stéphane ; Maguet, Arnaud ; Maltaverne, Emilie ; Mariën, Cyrille ; Martin, Bernhard ; Mayor, Genêt ; Mestre, Marie-Eve ; Millagou, Olivier ; Morrison, Paul ; Mrzyk, Petra ; Moriceau, Jean-François ; Murakami, Takashi ; Nara, Yoshimoto ; Noble, Paul ; Nottellet, Olivier ; Okamoto, Naoko ; Panighi, Gérald ; Parreno, Philippe ; Pastor-Lloret, Géraldine ; Peinado, Bruno ; Pelletier, Sandrine ; Pinard, Guillaume ; Quardon, Françoise ; Rebecq, Maroussia ; Rittener, Didier ; Ritter, Paul Nicolas ; Robert-Tissot, Christian ; Rondinone, Ugo ; Roy, Michaël ; Rullier, Jean-Jacques ; Scurti, Franck ; Séchas, Alain ; Soudre, Raphaël ; Steiner, Stéphane ; Trehin, Gilles ; Trenet, Didier ; 3e Hypothèse ; Verna, Jean-Luc ; de Vilhena, João ; West, Franz ; Wicker, Jean-Michel ; Yamasaki, Junko ; Zoritchak, Thomas ; etc.
Frans
Engels
Exhibition. Lee 3 Tau Ceti Central Armory Show. Villa Arson Nice. 06.07.2003 -12.10.2003
boek